Thermal, mechanical and viscoelastic properties of citric acid-crosslinked starch/cellulose composite foams. (15th February 2020) - Hassan, M.M.; Tucker, N.; Le Guen, M.J.
Graphical abstract: Highlights: Cellulose fibre-reinforced starch foams were fabricated by a simple method. Crosslinking with citric acid improved the water barrier and flexural properties. Crosslinked foams exhibited high tensile strength, superior to starch/cellulose foam. Composite foams showed superior thermal stability compared to starch/cellulose foam. Developed foams could be used for packaging fruits and vegetables in supermarkets. Abstract: In this work, biodegradable starch/cellulose composite foams were fabricated at 220 °C by compression moulding gelatinised starch containing cellulose fibres as a reinforcing agent and citric acid as a cross-linking agent. It was found that the stiffness, tensile strength, flexural strength, and hydrophobicity of the starch/cellulose composite foams increased, and water absorption capacity decreased with an increase in the concentration of citric acid. The tensile strength increased from 1.76 MPa for 0 % citric acid to 2.25 MPa for the starch/cellulose composite foam crosslinked with 5 % (w/w) citric acid. Similarly, the flexural modulus also increased from 445 MPa to 601.1 MPa, and the flexural strength from 3.76 MPa to 7.61 MPa, for the composite foam crosslinked with 5 % (w/w) citric acid. The crosslinked composite foams showed better thermal stability compared to the non-crosslinked composite foam. The resulting composite foams could be used as a biodegradable alternative to expanded polystyrene packaging.